Do tourists really intend to revisit Kota Bharu Cultural Heritage Zone? - Nik Mohd Aizat Nik Mohd Adib; Syakir Amir Ab Rahman; Shunji Suzuki; Nor Nadiah Najib (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cultural and heritage values in most countries have been recognized as resource of social and economic development. However, due to the post modernization of tourism attractions recently has affected few old and heritage sites. Sense of place is believed as one the factors to support the tourists’ motivation including revisiting the place. The study aims to assess the tourists’ motivation to revisit and the sense of place in Kota Bharu Cultural Heritage Zone. 445 questionnaire survey were distributed among domestic and international tourists and were analyzed using ANOVA test. The result indicates that sense of place in Kota Bharu Cultural Heritage Zone does not influence the tourists’ motivation to revisit. The study recommends the state government, local authorities and tourism players to enhance and rejuvenate the ambience of the heritage zone, in order to improve the number of tourist’s arrival to Kelantan hence sustaining the local economic.